2014
DOI: 10.1007/s40620-014-0143-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient removal of colistin A and B in critically ill patients undergoing CVVHDF and sorbent technologies

Abstract: Background Colistin pharmacokinetics data are scarce regarding patients undergoing renal replacement therapy (RRT), or even absent as in patients treated with sorbent technologies potentially capable of removing colistin by extensive absorption on many polymeric materials.Methods Twelve septic shock patients with acute kidney injury (AKI) undergoing RRT [continuous venovenous hemodiafiltration (CVVHDF) n = 7, coupled-plasma filtration adsorption-HF (CPFA-HF) n = 4, hemoperfusion n = 1] treated with colistin me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
3
7
0
1
Order By: Relevance
“…Colistin methanesulfonate and formed colistin are efficiently cleared by intermittent and continuous renal support modalities; less information is available for SLED than for shorter forms of IHD and CRRT . Supplementary doses of CMS are needed for patients receiving IHD or SLED.…”
Section: Clinical Questions and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colistin methanesulfonate and formed colistin are efficiently cleared by intermittent and continuous renal support modalities; less information is available for SLED than for shorter forms of IHD and CRRT . Supplementary doses of CMS are needed for patients receiving IHD or SLED.…”
Section: Clinical Questions and Recommendationsmentioning
confidence: 99%
“…Colistin methanesulfonate and formed colistin are efficiently cleared by intermittent and continuous renal support modalities; less information is available for SLED than for shorter forms of IHD and CRRT. 6,33,[70][71][72][73][74][75][76][77] Supplementary doses of CMS are needed for patients receiving IHD or SLED. IHD, SLED, and CRRT, each removes~10% of colistin an hour necessitating replacement of 10% of the daily dose per hour on these modalities.…”
Section: Does Renal Replacement Therapy Have Implications For Smentioning
confidence: 99%
“…Adequacy and dose adjustment of antibiotic therapy during CRRT are important issued, and several reports in literature warn against that the risk of underdosage. For instance, the extracorporeal drug removal for antibiotics used against MDR gram-negative infections has been established in literature [32] . Despite the appropriateness of antibiosis being retrospectively addressed in our study, the retrospective nature of this study prevented us from obtaining data on antibiotic concentrations during CRRT treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A further study reported relatively high SA during CVVHDF (0.42 for colistin A and 0.48 for colistin B) with a high extent of colistin removal, suggesting the dose should not be reduced (89). In patients with septic shock and AKI undergoing coupled plasma filtration-adsorption/CVVHDF or hemoperfusion with polymyxin B fiber cartridges, colistin removal was high, especially in the case of coupled plasma filtration-adsorption/CVVHDF; however, the short duration of hemoperfusion probably resulted in very little impact on total-body colistin content (90). Regarding PK of colistin during IHD, a case report analyzed the variations in colistin plasma levels in 2 patients with pneumonia from multidrug-resistant Gram-negative bacteria and AKI undergoing 4-h IHD; 2 million IU q12h has been suggested as the most appropriate dose in patients undergoing daily IHD (91).…”
Section: Polymyxinsmentioning
confidence: 99%